Imágenes de la violencia. Los retos de la justicia transicional y su costo emocional - Velázquez, Tesania (2015)
The present article reports on preliminary results of a research inthe psychosocial impact of transitional justice in Peru, after ten years of the Final Report of the Truth and Reconciliation Committee - TRC. Its general objective was to learn about the perceptions on transitional justice processes, particularly in the case of the TRC in Peru. Graphics and discursive materials that account for individual and collective narrative of direct and no direct victims in Huamanga were analyzed, which were obtained as part of a larger study on the psychosocial impact of the Truth and Reconciliation Committee - CVR. The results suggest that there are different expe- riences of violence that are characterized by being recurrent and continuous in time despite transitional justice processes and that the processes have emotional costs but also benefits that allow us to build democratic coexistence in a society.